Amblyseiinae of New Zealand (Acari: Phytoseiidae): redescriptions, rediscoveries, new records, new combinations and keys to species - Ma, Min; Fan, Qing-Hai; Zhang, Zhi-Qiang (Zootaxa, 2019)
This paper presents several new additions and changes to the subfamily Amblyseiinae of New Zealand. Amblyseius lentiginosus Denmark & Schicha, 1974 is newly recorded in New Zealand and its males and females are redescribed in detail. Amblyseius obtusus was recollected and a revised key to New Zealand species of Amblyseius is provided. Proprioseiopsis lenis (Corpuz & Rimando, 1966) is reported from New Zealand for the first time and its females are described in detail. A key to New Zealand species of Proprioseiopsis is also included. A rare species, Phytoscutus acaridophagus (Collyer, 1964), was rediscovered and its males and females are redescribed in detail. Three species, two in Amblyseius and one in Proprioseiopsis, are transferred to the genus Graminaseius: G. bidibidi (Collyer, 1964) comb. nov., G. martini (Collyer, 1982) comb. nov. and G. exopodalis (Kennett, 1958) comb. nov. Graminaseius has not been previously recorded in New Zealand.